Evaluating monetary policy options for managing resource revenue shocks when fiscal policy is laissez-faire: Application to Nigeria - Chuku Agbai Chuku (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
This study considers the implications of alternative monetary policy regimes to deal with a laissez-faire fiscal policy rule, where the government completely spends resource revenue windfall contemporaneously. A three sector dynamic stochastic general equilibrium model, which features key structural characteristics of resource-rich developing economies, such as; the Dutch disease, limited international capital mobility, credit constrained consumers, and limited labour mobility are core ingredients of the model. The model is calibrated to match the Nigerian economy. Three alternative mainstream monetary policy regimes are considered: i) a flexible exchange rate regime; ii) a crawling peg; and iii) a money growth target. The results show that the macroeconomic responses to these monetary policy regimes, depends on other auxiliary polices of the central bank, such as; sterilization policy, foreign reserve accumulation policy and openmarket operations. In particular, we find that a flexible exchange rate regime with full domestic absorption delivers the highest level of aggregate employment, though with higher volatility for other macroeconomic variables. The other policy rules deliver lower macroeconomic volatility but at the cost of crowding-out the private sector, depending on the mix of open-market operations. In welfare terms, policy regime (i) delivers the best outcome to economic agents.
Keywords: F41; E30; E58; E63; 330; windfall spending; monetary policy; Dutch disease; New Keynesian models